Analysis of the Effect of Fly Ash Waste Utilization as the Main Material in Polymer Brick Production on Mechanical and Physical Properties - Rajiman Rajiman; Dwiki Faiz Nugroho (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the effect of utilizing fly ash waste as the main raw material in the production of polymer bricks on the mechanical and physical properties of the resulting material. This research employed an experimental laboratory method by producing fly ash-based polymer brick specimens activated using alkaline solutions of NaOH and Na₂SiO₃. The curing temperatures applied in this study were 70°C, 80°C, and 90°C. The tests conducted included compressive strength tests and water absorption tests. The results showed that the utilization of fly ash as the primary material significantly influences the increase in compressive strength of polymer bricks. The highest compressive strength value was obtained at higher curing temperatures, indicating that an increase in curing temperature accelerates the geopolymerization process and produces a denser and stronger material structure. In addition, the water absorption test results indicated that the polymer bricks have relatively low water absorption values, which reflects low porosity and good material quality. Therefore, fly ash-based polymer bricks have strong potential as an environmentally friendly alternative building material, energy-efficient, and possessing good mechanical performance, making them a sustainable solution for industrial waste utilization